The Illocutionary Force of Inuit Ice Vocabularies - Shields, Rob (Journal of Northern Studies, 2020)
Lexicons of Yup’ik sea-ice terminology rely on extra-textual elements, including photographs, diagrams and sketches. Definitions are also supplemented with stories about personal experience and of the behaviour of ice phenomena. Speech act theory argues that these elements communicate an often overlooked illocutionary dimension which shows the importance of semantics in addition to the syntax of scientific definitions. The illocutionary aspects captures the performative, experiential quality of sea ice as a lived environment engaged in processes of hunting, travel and fishing. I argue that the illocutionary force of the descriptions presented in the lexicons is epistemic and ignoring this silences the Indigenous “voice.” This supports Townsends argument that illocutionary silencing occurs when science treats environmental descriptions as not material but cultural and circumstantial.